Contribution of the informal economy at Thabo Mofutsanyane District Municipality - F. P. Mothamaha; K. Sibanda (Путеводитель предпринимателя)
This study aimed to delineate the contributions of informal businesses to the economy of the Thabo Mofutsanyane District Municipality in the Free State Province, South Africa. The study employed a quantitative research methodology. The study’s sample size comprised 333 respondents, chosen using the Conroy sampling table 1. A total of 333 questionnaires were distributed, of which 232 were completed and returned, yielding a response rate of 70%. A robust positive association has been demonstrated between skill development, poverty alleviation, and job creation. The study revealed that informal entrepreneurship significantly contributes to GDP, local economic growth, and serves as a source of livelihood, employment creation, income generation, and survival for informal entrepreneurs. Robust stakeholder involvement and the incorporation of the informal economy were recommended in this paper.